Gender evaluation methodology for Internet and ICTS: A learning tool for change and empowerment. - Cinco, Cheekay; Garcia Ramilo, Chat (Association for Progressive Communications, APC Women's Networking Support Programme, 2005)
GEM is not only a tool for gender evaluations. Nor is it just a guide or a manual that breaks down gender concepts and makes it relevant for ICT projects. GEM is also a project and a community. GEM as a project germinated in January 2000. A workshop, held in a small Manila hotel in the Philippines, was the seed that grew into a fouryear undertaking. About 30 women, mostly members of APC WNSP, reflected on almost 10 years of women’s networking in an attempt to build a collective understanding of the real impact of our work in changing women’s lives. But instead of arriving at definitive answers, we ended up asking more questions about change, empowerment and ICTs. What changes are empowering for women? how do these changes shift gender relations between women and men? how can we tell if ICTs are making a difference in these changes? how do we measure these changes? These questions led to months of research, meetings and painstaking writing. At that time, evaluations of ICT projects were very hard to come by. Evaluation tools for ICT projects were only beginning to be explored, mainly through the work of the International Development Research Centre which was developing an evaluation framework for ICTs for development projects. APC WNSP provided the gender related perspective in this endeavour through proposals around building gender considerations in evaluation frameworks that were largely gender neutral.
Keywords: 2000 à aujourd'hui; méthodologie; outils; ouvrages de références; projet charge mentale; pédagogie; périodes historiques; ressource en ligne; technologie; thématiques

Sains et saufs : petit manuel de lutte contre l'homophobie à l'usage des jeunes - Dorais, Michel; Verdier, Éric (Des hommes et des femmes en changement, 2005)
Keywords: EDI; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; identités LGBTQIA2+; intervention sociale; justice sociale; premier cycle; psy4910; pédagogie; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; violences

Un parcours en contre point entre les sciences et les techniques, le féminisme et le genre - Fassa, Farinaz (Nouvelles Questions Feministes, 2005)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; inégalités; maternité; pays-bas; premier cycle; privilèges; pédagogie; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Whose Culture Has Capital? A Critical Race Theory Discussion of Community Cultural Wealth - Yosso, Tara J. (Race, Ethnicity and Education, 2005)
This article conceptualizes community cultural wealth as a critical race theory (CRT) challenge to traditional interpretations of cultural capital. CRT shifts the research lens away from a deficit view of Communities of Color as places full of cultural poverty disadvantages, and instead focuses on and learns from the array of cultural knowledge, skills, abilities and contacts possessed by socially marginalized groups that often go unrecognized and unacknowledged. Various forms of capital nurtured through cultural wealth include aspirational, navigational, social, linguistic, familial and resistant capital. These forms of capital draw on the knowledges Students of Color bring with them from their homes and communities into the classroom. This CRT approach to education involves a commitment to develop schools that acknowledge the multiple strengths of Communities of Color in order to serve a larger purpose of struggle toward social and racial justice.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; sciences de l'éducation; sex2283; thématiques; théorie critique de la race

Peut-on enseigner le féminisme à l’Université ? - Zaidman, Claude (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2005)
Une des façons d'interpréter le titre de ces journées est de s'interroger sur la transmission entre les générations c'est-à-dire sur la relève en Etudes féministes. Je suis heureuse de pouvoir constater, grâce à ces journées et aux journées précédentes organisées par EFiGiES avec l'aide du RING, à quel point nous pouvons être rassurées sur ce point : il existe une relève et, qui plus est, une relève qui innove tant dans les thématiques que dans les façons de s'organiser et de travailler.
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; approches et analyses; justice sociale; pédagogie; périodes historiques; ressource en ligne; thématiques; université